2018
DOI: 10.1124/jpet.117.247163
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Novel Receptor-Interacting Serine/Threonine‐Protein Kinase 2 Inhibitors Using Structural Similarity Analysis

Abstract: Receptor-interacting protein kinase 2 (RIP2 or RICK, herein referred to as RIPK2) is linked to the pathogen pathway that activates nuclear factor -light-chain-enhancer of activated B cells (NFB) and autophagic activation. Using molecular modeling (docking) and chemoinformatics analyses, we used the RIPK2/ponatinib crystal structure and searched in chemical databases for small molecules exerting binding interactions similar to those exerted by ponatinib. The identified RIPK2 inhibitors potently inhibited the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…We hypothesized that abnormalities in signaling proteins upstream from NF-κB, such as in RIPK2 may exist. Analysis of RIPK2 activation in IBC cell lines and patient tumor tissues revealed elevated kinase activity as determined by the surrogate detection tool, the use of a RIPK2 phospho antibody phosphorylated at Serine-176 (S176 indicative of active RIPK2) [ 27 , 49 ] and tyrosine-474 recognizing the autophosphorylation sites of RIPK2 (also indicative of active RIPK2) [ 50 ]. IBC cells lines show robust active RIPK2 when compared to non-IBC cell lines ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that abnormalities in signaling proteins upstream from NF-κB, such as in RIPK2 may exist. Analysis of RIPK2 activation in IBC cell lines and patient tumor tissues revealed elevated kinase activity as determined by the surrogate detection tool, the use of a RIPK2 phospho antibody phosphorylated at Serine-176 (S176 indicative of active RIPK2) [ 27 , 49 ] and tyrosine-474 recognizing the autophosphorylation sites of RIPK2 (also indicative of active RIPK2) [ 50 ]. IBC cells lines show robust active RIPK2 when compared to non-IBC cell lines ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…WEHI-345, which was identified as a RIPK2 inhibitor by screening a proprietary library of 120 kinase inhibitors, delayed NF-κB activation by inhibiting polyubiquitination of RIPK2 and ameliorated experimental autoimmune encephalomyelitis (Nachbur et al, 2015). Salla et al (2018) identified and characterized two novel RIPK2 inhibitors by using molecular modeling and chemoinformatics analysis (Salla et al, 2018). The degree of suppression in DSSinduced colitis was significantly greater in mice treated with these RIPK2 inhibitors than in those treated with gefitinib (Salla et al, 2018).…”
Section: Nod2-ripk2 and Tlrs-ripk2 Axes In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Salla et al (2018) identified and characterized two novel RIPK2 inhibitors by using molecular modeling and chemoinformatics analysis (Salla et al, 2018). The degree of suppression in DSSinduced colitis was significantly greater in mice treated with these RIPK2 inhibitors than in those treated with gefitinib (Salla et al, 2018). Although these studies utilizing RIPK2 inhibitors have not clearly shown whether such small molecules suppressed the activity of the NOD2-RIPK2 and TLRs-RIPK2 pathways to improve inflammation, their therapeutic and preventive effects seen in experimental IBD allow considering RIPK2 as a new therapeutic target in human IBD.…”
Section: Nod2-ripk2 and Tlrs-ripk2 Axes In Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This work is the first to demonstrate the efficacy and modulatory activity of a RIP2 targeting compound using a clinically relevant model of allergic asthma. Numerous inhibitors have both been discovered and developed for modulation of RIP2 activity (23,(35)(36)(37)(38)(39)(40)(41)(42)(43). The RIP2 inhibitor utilized in this study, GSK583, has been reported to be highly selective and exhibits strong potency even in vivo (23,39).…”
Section: Discussionmentioning
confidence: 99%